Aircraft Cabin Air Sampling Study: Part 1 of the Final Report - Crump, Derrick; Harrison, Paul; Walton, Christopher (Cranfield University, 2011)
This report describes the methodology and results of a study of aircraft cabin air quality undertaken by Cranfield University and two contracted analytical laboratories on behalf of the Department for Transport (DfT). The project began in 2007 and was carried out under the leadership of the late Helen Muir OBE (Professor of Aerospace Psychology, Cranfield University) until her illness and untimely death in the first quarter of 2010. The authors and project team are indebted to Helen for her inspiring contribution that made this project and our report possible. She is sadly missed.